Optimization of Social Welfare Based on Two Distinct Decentralized P2P Energy Sharing and Pricing Mechanisms - Zan, Jia (Smart grids and sustainable energy, 2025)
This study develops and evaluates two decentralized peer-to-peer energy sharing and pricing mechanisms with the goal of improving social welfare and lowering overall grid use. The first mechanism, which uses a seven-step market-clearing algorithm, allows prosumers to trade energy directly. The second introduces a fallback operator-managed system that handles unmatched bids to maintain network balance and continuity. Both mechanisms work without intermediaries, ensuring participant autonomy and anonymity. The study developed a two-step pricing technique. It incorporated prosumer preferences including energy source type and trade reputation using premium coefficients. A distributed primal-dual sub-gradient algorithm enables efficient and fair market clearing while maintaining budget balance and individual rationality. Simulations were carried out on the IEEE European Low Voltage Test Feeder with 55 prosumers, including photovoltaic-equipped homes. The network was divided into four zones, and energy matching favored peers based on their contributions, green energy usage, and reputational rankings. Proposed model reduced grid reliance by 28.4% while also improving the energy-sharing sustainability index by 9.08%. Energy prices were tightly connected with Feed-in Tariff values, and the dynamic pricing mechanism effectively regulated peak demand by responding to real-time supply-demand ratios. The simulation data is produced from realistic yet synthetic energy profiles applied to a typical test network. These findings demonstrate the potential for the proposed decentralized peer to peer system to improve efficiency, equality, and scalability in future smart grid applications.